Principal Challenges in Addressing School Bullying Through Peer Empowerment Approaches in Elementary Schools - Mohammad Bilutfikal Khofi; Makherus Sholeh (Journal of Elementary Education Research and Practice, 2025)
This study examines the challenges faced by school principals in implementing peer empowerment approaches to address bullying in elementary schools. A Systematic Literature Review (SLR) was conducted in accordance with PRISMA guidelines. Twelve peer-reviewed articles published between 2015 and 2025 were selected from reputable databases, including Scopus, Web of Science, ERIC, Google Scholar, DOAJ, and Garuda. Data were analyzed using thematic analysis to identify recurring psychosocial barriers and leadership-related challenges in the implementation of peer-based anti-bullying programs. The findings reveal four dominant barriers: diffusion of responsibility, students’ fear of becoming subsequent victims, pluralistic ignorance, and observers’ limited knowledge of appropriate intervention strategies. Collectively, these factors contribute to a pattern of collective passivity that weakens students’ capacity to function as active bystanders in bullying prevention. Furthermore, the effectiveness of peer empowerment programs is strongly contingent upon principals’ leadership capacity to cultivate a safe, supportive, and prosocial school climate. This includes the implementation of witness protection mechanisms, the correction of erroneous social norms, the strengthening of moral courage literacy, and the provision of evidence-based intervention training.